Effect of Race and Ethnicity on Antihypertensive Medication Utilization Among Women in the United States: Study of Women's Health Across the Nation (SWAN). Issue 3 (March 2017) - Jackson, Elizabeth A.; Ruppert, Kristine; Derby, Carol A.; Lian, Yinjuan; Neal‐Perry, Genevieve; Habel, Laurel A.; Tepper, Ping G.; Harlow, Siobán D.; Solomon, Daniel H.
Abstract : Background: Antihypertensive medication use may vary by race and ethnicity. Longitudinal antihypertensive medication use patterns are not well described in women. Methods and Results: Participants from the Study of Women's Health Across the Nation (SWAN), a prospective cohort of women (n=3302, aged 42–52), who reported a diagnosis of hypertension or antihypertensive medication use at any annual visit were included. Antihypertensive medications were grouped by class and examined by race/ethnicity adjusting for potential confounders in logistic regression models. A total of 1707 (51.7%) women, mean age 50.6 years, reported hypertension or used antihypertensive medications at baseline or during follow‐up (mean 9.1 years). Compared with whites, blacks were almost 3 times as likely to receive a calcium channel blocker (odds ratio, 2.92; 95% CI, 2.24–3.82) and twice as likely to receive a thiazide diuretic (odds ratio, 2.38; 95% CI, 1.93–2.94). Blacks also had a higher probability of reporting use of ≥2 antihypertensive medications (odds ratio, 1.95; 95% CI, 1.55–2.45) compared with whites. Use of angiotensin‐converting enzyme inhibitors/angiotensin receptor blockers and thiazide diuretics increased over time for all racial/ethnic groups. Contrary to our hypothesis, rates of β‐blocker usage did not decrease over time. Conclusions: Among this large cohort of multiethnic midlife women, use of antihypertensive medications increased over time, with angiotensin‐converting enzyme inhibitors/angiotensin receptor blockers becoming the most commonly used antihypertensive medication, even for blacks. Thiazide diuretic utilization increased over time for all race/ethnic groups as did use of calcium channel blockers among blacks; both patterns are in line with guideline recommendations for the management of hypertension.